Mainland China and western trade credits - K. Reese (Intereconomics, 1976)
The author discusses the question whether autarky will remain a central national policy goal in Peking after the present ruling group relinquishes power. He comes to the conclusion that, although China's foreign trade particularly with the Western world will expand rapidly, Peking will continue its abstinence from foreign trade credits.
Keywords: 330; Foreign Trade